Bronchial Asthma in a Hot Climate: Interaction of Clinical Status, Lung Function and Environmental Factors - Bekmurodovna, Tosheva Khakima (American Journal of Biomedicine and Pharmacy, 2025)
Bronchial asthma is a chronic inflammatory disease of the airways characterized by bronchial hyperreactivity and reversible airway obstruction. Climate conditions, particularly hot climates, can exacerbate the clinical course of asthma, affecting both symptoms and lung function. High temperatures, dry air, and increased exposure to environmental allergens (such as dust and pollen) pose significant challenges for asthma patients.